Muslim Friend7 Ly Tourism and Accommodation of Malaysian Hotel Industries - BANGSAWAN, S.; MS, M.; RAHMAN, M. M; RAZIMI, M. S.A (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Malaysia is one of the countries that attract tourist from all over the world. There is no barrier for the tourist to select from a range of halal products and hotel services available. Therefore, several potential attributes of Muslim friendly hotel services were analyzed from two major tourist destination state of Malaysia, namely Kedah and Penang. The analysis was based on three major online accommodation service providers. The findings revealed the significant information of the Muslim friendly hotel services in Malaysia. Therefore, updating the current information of the Muslim friendly tourism services is recommended. RESUMEN Malasia es uno de los países que atrae a turistas de todo el mundo. No hay ninguna barrera para que el turista seleccione entre una gama de productos halal y servicios de hotel disponibles. Por lo tanto, se analizaron varios atributos potenciales de servicios hoteleros amigables para los musulmanes en dos de los principales destinos turísticos de Malasia, a saber, Kedah y Penang. El análisis se basó en tres proveedores principales de servicios de alojamiento en línea. Los hallazgos revelaron la importante información de los servicios de hotel musulmanes amigables en Malasia. Por lo tanto, se recomienda actualizar la información de los servicios turísticos musulmanes amigables.